Fresno County Bar Association Luncheon With Keynote Speaker Fresno Mayor Dan Whitehurst - Watkins, Howard::::::::: (1982)
Robert Oliver and Doug Jensen watching Dan Whitehurst speaking The Fresno Hilton signs on lectern